The Effect of Distribution and Promotion on Customer Satisfaction and the Impact on Customer Loyalty in the ProductNestle Indonesia in Aceh Besar (International Journal of Scientific Research and Management (IJSRM), 2024)
This research aims to see the Distribution and Promotion effect on Customer Satisfaction and its impact on Customer Loyalty of Nestle Indonesia company in Aceh Besar. The population was all customers of Nestle Indonesia in Aceh Besar Regency. Samples were determined based on Structural Equation Modeling (SEM) analysis using the formula 10 times the number of indicator variables, totaling 18 indicators used, totaling 180 samples. Data were processed using SEM. The results show that Distribution influences Customer Satisfaction, Promotion influences Customer Satisfaction, Distribution influences customer loyalty, Promotion influences Customer Loyalty, Customer Satisfaction influences Customer Loyalty, Customer Satisfaction mediates the Distribution effect on Customer Loyalty, and Customer Satisfaction mediates the Promotion effect on Customer Loyalty. These findings explain the presence of Distribution and Promotion variables which can have an impact on customer loyalty through customer satisfaction. Interestingly, partial mediation plays a role in customer satisfaction, so distribution and promotion can influence customer loyalty both directly and indirectly. This premise can be developed by adding new variables in further research.